Voiceless subjects? Research ethics and persons with profound intellectual disabilities. Issue 3 (4th May 2017) - Mietola, Reetta; Miettinen, Sonja; Vehmas, Simo
Abstract: This paper discusses possibilities of designing ethical research practice in relation to people with profound intellectual and multiple disabilities (PIMD). We will argue that in the case of this group of people, research ethics is about ethically justifiable research aims, design, methods, and practices that are based on the recognition of their equal worth as humans. We argue that the turn to emancipatory methods in disability studies has effectively excluded persons with PIMD as they implicitly assume that research participants have the kind of cognitive and communicative capacities that persons with PIMD lack. Their exclusion from disability studies is further reinforced by the theoretical tradition of the field that has emphasised the material arrangements of society, as well as the ableist cultural ideologies as key factors contributing to disabled people's social exclusion. It is problematic to apply these approaches to individuals whose lives are marked by insurmountable impairment effects. Research ethics should take into account potential disparities of cognitive ability and power between researchers and research participants. Using an ongoing ethnographic study about the lives of persons with PIMD as an example, we describe in detail what positioning research participants as moral subjects could mean in practice.